PENGARUH DAYA TARIK WISATA, AKSESIBILITAS, DAN KEPUASAN WISATAWAN TERHADAP MINAT BERKUNJUNG KEMBALI (Study kasus pada Objek Wisata Budaya Taman Tujuh Desa Hiang Sakti) - Anggia Ayu Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Abstract: The purpose of this study was to determine and analyze the influence of tourist attraction, accessibility, and tourist satisfaction on the cultural tourism object of Taman Tujuh Hiang Sakti Village, Sitinjau Laut District, Kerinci Regency, Jambi Province. The type of data used is primary data is quantitative. The primary data was obtained from distributing questionnaires to tourists who visited the cultural tourism object of Taman Tujuh Hiang Sakti Village. Respondents amounted to 80 people. The results showed that the demographic characteristics of visitors to the Taman Tujuh cultural tour were the majority aged 17-27 years, were female, had an undergraduate degree and were students. Based on multiple regression analysis, it shows that the variable tourist attraction (X1) Accessibility (X2) and Tourist Satisfaction (X3) have a significant effect on Interest in Returning to the cultural tourism object Taman Tujuh Hiang Sakti village. This research has implications that Hiang Sakti village needs to carry out more intensive promotions and offer even better wosata product offers. Keywords: Tourist Attraction, Accessibility, Tourist Satisfaction and Interest in Returning